Эфирные масла некоторых видов рода Rhododendron L; Химия растительного сырья; № 3 - Белоусов М. В. Михаил Валерьевич; Басова Е. В.; Юсубов М. С. Мехман Сулейман-оглы (Сулейманович); Березовская Т. П.; Покровский Л. М.; Ткачев А. В. (2000, 2000)
Заглавие с экрана